Precede-Procede Analysis of Prenatal Class Plus Model in the Optimization Education of High Risk Pregnancy - Azinar, Muhammad; Fibriana, Arulita Ika; Wahyuningsih, Anik Setyo; Azam, Mahalul (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
High-risk pregnancies are still common in rural areas. The percentage of high-risk pregnancy in Singorojo sub-district of Kendal District in the last three years has increased significantly. The highest number of cases was in Cening and Singorojo villages. In the past year, 86.88% of pregnancies in Cening village and 55.42% of pregnancies in Singorojo village were categorized as high-risk. The lack in community education limited prevention of high-risk pregnancies. Prenatal Class Plus model is an innovation that was being developed in this study. This is a research and development study with qualitative and quantitative approaches. The Ã¢â‚¬Å“Prenatal Class PlusÃ¢â‚¬Â model was developed in Cening and Singorojo village. Research subjects were pregnant women, husbands, or families of pregnant women, health cadres, and related stakeholders. Research data were analyzed qualitatively and quantitatively. Prenatal Class Plus model can improve the knowledge, attitude and efforts of pregnant women and their husbands during parturition and prevention of pregnancy complications (P4K).